A Balanced Geological Cross-Section along Kohalpur – Surkhet Area of Sub-Himalayan Range, Mid-Western Nepal - Kafle, Nirmal; Dhungel, Lelin Raj; Acharya, Kamala Kanta; Dhital, Megh Raj (Journal of Science and Engineering, 2019)
The Sub-Himalayans Zone comprises a tectonic wedge of syn-orogenic sediments along the outer Himalayan Belt. Sediments are integrated into the accretionary prism from the foreland Indo-Gangetic plain, undergo a tectonic cycle within it, and eventually are eroded. The structural sketch map unveils westward-plunging arcuate structures on the leading location of the Outer Belt. A balanced cross-section has been constructed across the Sub-Himalayan Hills of the Kohalpur-Surkhet region of mid-western Nepal in order to determine the structural geometry of the region and to calculate tectonic shortening. The mid-western Nepal Sub-Himalaya has an emergent splay fan geometry with no major prevailing thrust contains the Main Boundary Thrust (MBT), the Bheri Thrust, the Babai Thrust and the Main frontal Thrust (MFT) which are all imbricate of the main decollment which ramp up-section through the 5 km thick tectonic sedimentary prism. North-south shortening across the mid-western Nepal, Kohalpur-Surkhet section has been approximately 29 km, or 55% shortening.